Recreating agriculture-agroecological knowledge and peasant's identities in a process of education-research-action in Chiapas, Mexico - Katrin Aiterwegmair; Mateo Mier y Terán Giménez Cacho; Fernando Limón Aguirre; Ulli Vilsmaier; Juliana Merçon; José Fernando López Hernández; Romina Martínez Velarde (Universidade Federal do Norte do Tocantins, 2021)
The transdisciplinary and peasant-based process of education-research-action analysed in this article aims at the construction of agroecology in theory and practice by the peasants' organization OCEZ-CNPA in Chiapas, Mexico. Conducting a methodology based on Popular Education and Participatory Action Research, agri-cultural knowledge has been regenerated, constituting potential for profound agroecological transformation. This knowledge relies on identities and ways of life that, despite having been colonized, continue to have deep roots that resist the paradigm of modernity. The collective reflection of the peasants' experiences and biocultural memories have made the agri-cultural change induced by the 'green revolution' understood as an ontological and epistemological rupture. With this peasant-based and decolonial research, knowledge, values and practices, that have been characterizing the Mayan agriculture for thousands of years, have been reclaimed. This analysis has led to the conception of a deep agroecology that acknowledges and recovers the peasants' ontologies and epistemologies, constitutive of other paradigms, corresponding to forms of thinking of and living in the world that differs to those of the modern paradigm.